Synthesis of magnetic electroactive nanomotors based on sodium alginate/chitosan and investigation the influence of the external electric field on the mechanism of locomotion - Fariba Mafakheri; Ali Asakereh; Sepideh Khoee; Mojtaba Kamankesh (Scientific Reports, 2023)
Abstract In this paper, we report a novel electric-driven Janus nanomotor (JNMs) based on SPIONs nanoparticle decorated with chitosan (Cs) and sodium alginate (Na/Alg) using the Pickering emulsion method. The JNMs dispersed in aqueous media exhibit linear trajectories under DC electric field, and the driving force is attributed to the self-electro-osmotic mechanism and surface modifications. This study offers an approach to remotely control the motion modes of the JNMs, including start, stop, directional and programmable motion, which can be advantageous for various application scenarios. The diffusion coefficient and velocity of the JNMs were investigated through mean square displacement analysis for single particle of JNMs, both in distilled water and in the presence of different di and trivalent metal cations (Fe3+, Al3+, Ba2+, Ca2+ and Mg2+) as crosslinking agents, as well as monovalent salts (LiCl and KCl). The results revealed that the motion of JNMs was fastest in the presence of Fe3+ as crosslinker agent (about 7.2181 μm2/s) due to its higher charge than equimolar Na+ . Moreover, it was demonstrated that increasing the ionic strength led to relatively higher speeds of JNMs, as the solution polarity increased and, as a result, the driving force of electro-osmoesis enhanced.